La planification urbaine et la gestion foncière en Algérie : quelle durabilité ? Cas de la ville de Blida - Leila Saharaoui (Unité Mixte de Recherche 8504 Géographie-cités, 2021)
In Algeria, the National Agency for Spatial Planning (ANAT) reports over-consumption of land and an increasing rate of urbanization. Faced with this observation, a legislative and regulatory mechanism was promulgated between 1990 and 2000, making spatial planning a tool for sustainable territorial development. The article questions the effectiveness of the regulations and the legislative mechanism of urban planning through the analysis of the legal texts and their applicability through the actual urban planning instruments. Also, the article highlights dysfunctions inherent to the process of land management and land use in the urban environment, which can affect and compromise its sustainability. We support this study with the case of Blida, a town in the Mitidja region, which constitutes an agricultural national reservoir. It is currently undergoing the consequences of land speculation and fast-growing urbanization, and is exposed to the constraints of the unavailability of land to be urbanized.